2019
DOI: 10.5812/archcid.84452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Methods of Collecting Scorpions (Arachnida, Scorpiones) in Khuzestan Province, Southwestern Iran

Abstract: Background: Scorpions have evermore received considerable attention in Iran due to their medical importance, richness, and frequency. In order to the study scorpions' behavior and bio-ecology, it is important to use the proper method for scorpion catching. The collection and maintenance of the specimens are among the most important parts of every study. Objectives: This article investigated different techniques suitable for capturing scorpions in residential and non-residential areas of Khuzestan province, Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Pitfall trapping is considered an important method for collecting scorpions (Williams 1968, Druce et al 2004, Shehab et al 2011Dehghani et al 2019). Capture efficiency of pitfall traps, for collecting ground-active invertebrates, can be affected by trap material (Luff, 1975), use of trap covers (Spence & Niemelä, 1994), trap shape (Spence & Niemelä, 1994), size of trap diameter, preservative solutions, use of funnels, sampling intervals, and distance between adjacent traps (Brown and Matthews 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitfall trapping is considered an important method for collecting scorpions (Williams 1968, Druce et al 2004, Shehab et al 2011Dehghani et al 2019). Capture efficiency of pitfall traps, for collecting ground-active invertebrates, can be affected by trap material (Luff, 1975), use of trap covers (Spence & Niemelä, 1994), trap shape (Spence & Niemelä, 1994), size of trap diameter, preservative solutions, use of funnels, sampling intervals, and distance between adjacent traps (Brown and Matthews 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, about ten different methods have been used to collect scorpions, including stone rolling, pitfall trapping, water-pan traps, using UV light, destroying mud walls, pouring water into scorpion burrows, excavating channels, using rubber bands, using soaked cloth as traps, and collecting scorpions by stung patients (Dehghani et al 2019). Dehghani et al (2019) evaluated different methods, except pitfall trapping, for collecting these arthropods in Khuzestan province, and their results showed that using UV light and turning stones were the most efficient methods for collecting scorpions at night and during the day, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Pitfall trapping is considered an important method for collecting scorpions (Williams 1968, Druce et al 2004, Shehab et al 2011Dehghani et al 2019). Capture efficiency of pitfall traps, for collecting ground-active invertebrates, can be affected by trap material (Luff, 1975), use of trap covers (Spence & Niemelä, 1994), trap shape (Spence & Niemelä, 1994), size of trap diameter, preservative solutions, use of funnels, sampling intervals, and distance between adjacent traps (Brown and Matthews 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, about ten different methods have been used to collect scorpions, including stone rolling, pitfall trapping, water-pan traps, using UV light, destroying mud walls, pouring water into scorpion burrows, excavating channels, using rubber bands, using soaked cloth as traps, and collecting scorpions by stung patients (Dehghani et al 2019). Dehghani et al (2019) evaluated different methods, except pitfall trapping, for collecting these arthropods in Khuzestan province, and their results showed that using UV light and turning stones were the most efficient methods for collecting scorpions at night and during the day, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the type of climate, Iran is very rich in scorpions, so far, scorpions from three families have been reported in Iran. Iran is among the countries where many species of scorpions, especially dangerous ones, have been reported (18). A scorpion sting causes infection as well as poisoning.…”
mentioning
confidence: 99%